Analisis Efektivitas Mesin Press Baglog Menggunakan Metode Overall Equipment Effectiveness (OEE) di UD. Jamur Tiram - Masud, Mukhammad; Riyana, Iis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
UD Jamur Tiram is a business engaged in the cultivation and sale of oyster mushrooms. This company was established to meet the increasing market demand for oyster mushrooms and to empower the local community through business opportunities and job creation.The current problem faced by the company is frequent damage to the roller and cylinder of the baglog machine. This is caused by several factors, one of which is the lack of machine maintenance, and the materials used for making the oyster mushroom baglogs are not functioning optimally. Therefore, in addressing this issue, UD. Jamur Tiram aims to improve the effectiveness of the baglog press machine to ensure that it can meet all consumer demands by improving its production rate so that it is not hindered or halted.To enhance the effectiveness of the machine, research was conducted using the Overall Equipment Effectiveness (OEE) method. The results of this study indicate that the average effectiveness value of the baglog press machine at the beginning of December-January 2025 is 92,75%. This shows that the OEE (Overall Equipment Effectiveness) percentage meet the standard of 85%.